Tussen Antwerpen & Parijs: De 'Peter Benoit-piano' van Pleyel, Wolff & Cie, 1884 - De Paepe, Timothy 1981-; Dewilde, Jan; Aelvoet, Hannah; Wijnants, Yannick; Verhoeven, Patrick 1969-; De Ruyck, Stefaan; Caremans, Clement (Antwerp BAI, 2021)
In 2021, Yannick Wijnants (Atelier Herkenrode) completed the restoration of the so-called “Peter Benoit piano”, a concert grand piano by the firm Pleyel, Wolff & Cie from 1884. The restoration will allow music lovers, for the first time in decades, to reacquaint themselves with the warm sound of this magnificent instrument. Moreover, since the piano arrived in Antwerp in 1895, it has had an intriguing connection with one of Flanders' most famous composers: Peter Benoit (1834-1901). In this cahier, four experts tell more about the piano, about Peter Benoit and his piano repertoire and about its restoration. (Translated with Deepl.com)
Keywords: Benoît, Peter -- 1834-1901; Pleyel et Cie (France); 19th Century (1801-1900); Piano; Musical instrument makers; Antwerp (Belgium); Paris (France)